2021
DOI: 10.3389/fimmu.2021.810047
|View full text |Cite
|
Sign up to set email alerts
|

Development of an In Vivo Probe to Track SARS-CoV-2 Infection in Rhesus Macaques

Abstract: Infection with the novel coronavirus, SARS-CoV-2, results in pneumonia and other respiratory symptoms as well as pathologies at diverse anatomical sites. An outstanding question is whether these diverse pathologies are due to replication of the virus in these anatomical compartments and how and when the virus reaches those sites. To answer these outstanding questions and study the spatiotemporal dynamics of SARS-CoV-2 infection a method for tracking viral spread in vivo is needed. We developed a novel, fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…As we previously reported (Madden et al), studies in SARS-CoV-2 infected rhesus macaques were consistent with the intravenously (IV) injected probe being able to associate with and accumulate in SARS-CoV-2 infected cells, as also seen in tissue culture 24 . Based on the ability of the fluorophore labeled CR3022-F(ab')2 to reveal sites of SARS-CoV-2 infection within macaque tissues, we extended these studies to utilize a [ 64 Cu] -DOTA-labelled CR3022-F(ab')2 probe followed by detection in PET/CT scan.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…As we previously reported (Madden et al), studies in SARS-CoV-2 infected rhesus macaques were consistent with the intravenously (IV) injected probe being able to associate with and accumulate in SARS-CoV-2 infected cells, as also seen in tissue culture 24 . Based on the ability of the fluorophore labeled CR3022-F(ab')2 to reveal sites of SARS-CoV-2 infection within macaque tissues, we extended these studies to utilize a [ 64 Cu] -DOTA-labelled CR3022-F(ab')2 probe followed by detection in PET/CT scan.…”
Section: Introductionsupporting
confidence: 88%
“…It can be used to determine the precise location of infected cells in radioactive probe-guided necropsy. We have previously reported the early development of an in vivo antibody-based probe against SARS-CoV-2 utilizing fluorescent tagging of the F(ab')2 of the anti-spike IgG CR3022 24 . CR3022 was one of the first monoclonal antibodies identified that bound tightly to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation